Effects of messages emphasizing environmental determinants of obesity on intentions to engage in diet and exercise behaviors - NIEDERDEPPE, Jeff (Institutional Knowledge at Singapore Management University, 2013)
Reducing rates of obesity will require interventions that influence both individual decisions and environmental factors through changes in public policy. Previous work indicates that messages emphasizing environmental determinants increases support for public policies, but some suspect this strategy may undermine motivation to engage in diet and exercise. Emphasizing factors outside of personal control appears to enhance rather than undermine motivations to engage in healthy diet and exercise behavior.